2010
DOI: 10.1111/j.1600-0714.2010.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myofibroblasts in oral submucous fibrosis: correlation with disease severity

Abstract: Our results corroborate the possibility that OSMF actually represents an abnormal healing process in response to chronic mechanical and chemical irritation because of areca nut chewing as demonstrated by the increased incidence of myofibroblasts in this disease. Furthermore, the progressive increase in myofibroblasts from early to advanced stages suggests their potential use as markers for evaluating the severity of OSMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 32 publications
8
86
1
Order By: Relevance
“…The cellular mediator responsible for fibrosis is MF, which serves as collagenproducing cells when activated [31] . Continuous MF presence stimulates an abnormal repair mechanism, leading to excessive contraction and ECM secretion, subsequently causing fibrosis [30] . It was proposed that in fibrosis, MFs acquire an immune-privileged cell phenotype, which helps them to evade apoptosis and allows their uninterrupted accumulation [31] .…”
Section: Mfs In Oral Submucous Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular mediator responsible for fibrosis is MF, which serves as collagenproducing cells when activated [31] . Continuous MF presence stimulates an abnormal repair mechanism, leading to excessive contraction and ECM secretion, subsequently causing fibrosis [30] . It was proposed that in fibrosis, MFs acquire an immune-privileged cell phenotype, which helps them to evade apoptosis and allows their uninterrupted accumulation [31] .…”
Section: Mfs In Oral Submucous Fibrosismentioning
confidence: 99%
“…OSMF is an abnormal healing process in response to the chronic mechanical and chemical irritation caused by chewing areca nuts [30] . The cellular mediator responsible for fibrosis is MF, which serves as collagenproducing cells when activated [31] .…”
Section: Mfs In Oral Submucous Fibrosismentioning
confidence: 99%
“…Myofibroblasts were first identified in granulation tissue by Gabbiani and Majno (20) in 1972, and have been subsequently observed in a wide range of normal and abnormal tissues (21,22). Prior to the study by Gabbiani and Majno, there had not been an exact definition of myofibroblasts, as their appearance and function was not invariable within different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Tearing or shredding of flap, lingual gingiva, pterygomandibular raphe must be avoided. The wound healing mechanism of oral mucosa is faulty resulting in scarring and fibrosis [4]. Intra-alveolar extraction or 'simple' extraction of tooth also has to be performed with special care.…”
Section: Modification Of Surgical Techniquementioning
confidence: 99%
“…There is poor microcirculation in affected tissue, hypercoagulability of blood and medical treatment for this condition is not standardized [3]. It has been suggested that OSMF represents an abnormal healing process to chronic irritation [4].…”
Section: Introductionmentioning
confidence: 99%